Adaptation of respiratory chain biogenesis to cytochrome c oxidase deficiency caused by SURF1 gene mutations - Kovářová, Nikola; Čížková, Alena; Pecina, Petr; Stránecký, Viktor; Pronicka, Ewa; Kmoch, Stanislav; Houštěk, Josef (Biochimica et biophysica acta, 2012)
The loss of Surf1 protein leads to a severe COX deficiency manifested as a fatal neurodegenerative disorder, the Leigh syndrome (LS(COX)). Surf1 appears to be involved in the early step of COX assembly but its function remains unknown. The aim of the study was to find out how SURF1 gene mutations influence expression of OXPHOS and other pro-mitochondrial genes and to further characterize the altered COX assembly. Analysis of fibroblast cell lines from 9 patients with SURF1 mutations revealed a 70% decrease of the COX complex content to be associated with 32-54% upregulation of respiratory chain complexes I, III and V and accumulation of Cox5a subunit. Whole genome expression profiling showed a general decrease of transcriptional activity in LS(COX) cells and indicated that the adaptive changes in OXPHOS complexes are due to a posttranscriptional compensatory mechanism. Electrophoretic and WB analysis showed that in mitochondria of LS(COX) cells compared to controls, the assembled COX is present entirely in a supercomplex form, as I-III₂-IV supercomplex but not as larger supercomplexes. The lack of COX also caused an accumulation of I-III₂ supercomplex. The accumulated Cox5a was mainly present as a free subunit. We have found out that the major COX assembly subcomplexes accumulated due to SURF1 mutations range in size between approximately 85-140kDa. In addition to the originally proposed S2 intermediate they might also represent Cox1-containing complexes lacking other COX subunits. Unlike the assembled COX, subcomplexes are unable to associate with complexes I and III.
Keywords: mutace; Leigh Disease; Female; buněčné linie; Electron Transport Complex IV; Mitochondria; Cyclooxygenase 2; ženské pohlaví; Fibroblasts; podjednotky proteinů; Oxidative Phosphorylation; lidé; Electron Transport Complex III; respirační komplex IV; Electron Transport Complex I; respirační komplex I; Cytochrome-c Oxidase Deficiency; deficit cytochrom-c-oxidázy; mitochondriální proteiny; membránové proteiny; fibroblasty; Mutation; transport elektronů; Cell Line; mitochondrie; oxidativní fosforylace; Male; cyklooxygenasa 2; cyklooxygenasa 1; Cell Extracts; Protein Subunits; respirační komplex III; Membrane Proteins; Leighova nemoc; Mitochondrial Proteins; mužské pohlaví; Cyclooxygenase 1; Electron Transport; buněčné extrakty; Humans